2006
DOI: 10.1111/j.1540-4781.2006.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors Revised: Linguistic Knowledge and Metalinguistic Awareness in Second Language Gain in Russian

Abstract: The empirical study reported here investigated predictors of oral proficiency gain to the Advanced level resulting from immersion study abroad. The data consisted of 22 preimmersion Oral Proficiency Interviews (OPIs) of American students who participated in semester immersion programs in Moscow and St. Petersburg, and received a score of Intermediate High on the preimmersion OPI. On the basis of the students’ postprogram proficiency scores, the participants were grouped as learners who crossed the Advanced‐lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
2
18
2
1
Order By: Relevance
“…The quantitative evidence from this study showed, however, that students whose grammar knowledge was better did better on the speaking test, especially at the end of the stay, while the qualitative evidence suggested that the students who monitored the most gained the most. Both findings corroborate those of Golonka (2006), who found that grammar test scores were a significant predictor of intermediate L2 Russian learners' oral interview scores and that both these scores and the students' monitoring behavior (self-repair) clearly distinguished between ''gainers'' and ''null-gainers. ''…”
Section: Findings: the Larger Picturesupporting
confidence: 86%
See 1 more Smart Citation
“…The quantitative evidence from this study showed, however, that students whose grammar knowledge was better did better on the speaking test, especially at the end of the stay, while the qualitative evidence suggested that the students who monitored the most gained the most. Both findings corroborate those of Golonka (2006), who found that grammar test scores were a significant predictor of intermediate L2 Russian learners' oral interview scores and that both these scores and the students' monitoring behavior (self-repair) clearly distinguished between ''gainers'' and ''null-gainers. ''…”
Section: Findings: the Larger Picturesupporting
confidence: 86%
“…While a few studies have focused on listening (Allen, 2002;Kinginger, 2008), reading (Dewey, 2004;Kinginger, 2008), or writing (Freed, So, & Lazar, 2003), and a few others have documented three or four skills (Brecht, Davidson, & Ginsberg, 1995;Carroll, 1967;Gomes da Costa, Smith, & Whiteley, 1975;Lapkin, Hart, & Swain, 1995;Meara, 1994;Mizuno, 1998;Teichler & Maiworm, 1997), most research on the development of proficiency while abroad has concerned, not surprisingly, the speaking skill. Self-assessments of progress in this area have been very positive (see especially Teichler & Maiworm, 1997), but more objective measures have shown a mixed picture, with some showing substantial progress (Carlson, Burn, Useem, & Yachimowicz, 1991;Yager, 1998), and some more modest progress (Golonka, 2006;Huebner, 1995) or even none (Magnan, 1986).…”
Section: Previous Research About Growth In Oral Proficiency During Stmentioning
confidence: 99%
“…For example, O'Connor (1988) found that following a year abroad, college students who arrived in France with ACTFL ratings of Intermediate-Mid or High moved to Intermediate-High or Advanced (in Freed, 1995a). In a study of 22 college students with an Intermediate-Mid ACTFL rating in Russian prior to studying abroad, less than half of the participants improved their OPI scores over the course of a semester abroad (Golonka, 2006). While it is not surprising that absolute beginners would make significant strides in terms of language, it is interesting that three of the four participants in this study reached higher levels of proficiency than has been observed in other studies (Freed, 1995a;Golonka, 2006;O'Connor, 1988).…”
Section: Resultscontrasting
confidence: 40%
“…Much L2 self-repair research has focused on determining the frequency and distribution of the linguistic elements targeted for repairs (e.g., Bange & Kern, 1996;Fathman, 1980;Gilabert, 2007;Golonka, 2006;Griggs, 1998;Kormos, 1998;Lennon, 1984;Poulisse & Bongaerts, 1994;van Hest, 1996). This repair-typology-generating research has shown, in particular, that L2 speakers do not equally target all stages of the production process for repairs (e.g., Fathman, 1980;Lennon, 1984).…”
Section: Research On L2 Self Repairsmentioning
confidence: 99%